The Main Challenges Of Democratic Consolidation In Nigeria - Kamaljanova, Takhira; Azmukhanova, Aiman; Umirzakova, Lyazzat; Gaukhar, Almas (Opción, 2019)
The aim of the study is to target the main problems that impede the democratization of Liberia via comparative qualitative research methods. As a result, political conflict, gender issue, poverty, corruption, political forces and military rule are challenges which could prevent democratic consolidation in Nigeria. Besides, the major challenge of democratic consolidation in Nigeria is the ethnic complexity of the country which has generated intense and sometimes catastrophic political conflict. In conclusion, democracy was welcomed in Nigerian society with high expectation and hope. However, there were some obstacles in the way of democratic consolidation in Nigeria.